Pluralisme : Teologis atau Sosiologis? - Imam Wahyuddin (LPPM IAIN Sorong, 2015)
This article explores between pluralism as reality dan as sociology. The objective of this study is to analyze whether the pluralism is allowed and permitted or forbidden in Islam. So, the pluralism is not only permitted but also forbidden. In Islam thare are no true relativism. Tru relativism must be refused and rejected. This article again describes about the model of pluralism in Islam as Al-Quran studied to mans in the world.